Flood risk management in Europe innovation in policy and practice - Begum, Selina; Stive, M. J. F. (Marcel J. F.); Hall, Jim W. (Advances in natural and technological hazards research, 2007)
Brings together 26 articles on technical, socio-economic, environmental and policy aspects of flood risk management. These articles contribute to the five sections with the general themes: flood risk management practice, flood events and impacts, flood analysis and modelling; flood forecasting; and flood management policy.